Catalytic partial oxidation of propylene for acrolein production - Wibawanta, Sandra Anni Setyowati (Curtin University, 2011)
The objective of this thesis, which was to develop a high activity catalyst with 95% selectivity to acrolein at 350oC, was successfully achieved by Mo12Bi1.5Fe0.8Co3.5W0.6K0.04Si1.4P0.7Ox catalyst. The screening tests even when using propylene feed-stocks straight from the refinery by-product without prior purification have proven the consistency in catalytic performance, thereby confirming the reliability of the preparation technique. In trying to make the catalyst more robust, it was physically modified to spheres and pellets and was used successfully in a fixed bed reactor.